PERANCANGAN MEDIA INTERAKTIF TATA CARA SHALAT UNTUK ANAK USIA DINI - Fauzan Aulia; Syafwan .; Hendra Afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2012)
AbsractThe purpose of this design is to optimize and improve the attention and independence of early childhood in identifying and studying the movement of the prayer through interactive media. The required data for this design are gotten from observations, interviews, references and literature study from books and the internet. The method of this design uses SWOT analysis. Strength of interactive media designed, weakness of the media guide prayer graphical, opportunity and threat are viewed from result of observation. The result of this design is packaged in a CD. The information is packaged in the form of ordinances fard prayers, a few short letters, pillars of faith and the pillars of Islam.Kata kunci: perancangan, interaktif, optimal, shalat, dini